Proteomic Landscape of Cholangiocarcinomas Reveals Three Different Subgroups According to Their Localization and the Aspect of Non‐Tumor Liver. Issue 1 (19th December 2018) - Le Faouder, Julie; Gigante, Elia; Léger, Thibaut; Albuquerque, Miguel; Beaufrère, Aurélie; Soubrane, Olivier; Dokmak, Safi; Camadro, Jean‐Michel; Cros, Jérôme; Paradis, Valérie
Abstract : Purpose: Cholangiocarcinomas (CCs) define a heterogeneous entity based upon their anatomic localization (intra versus extrahepatic) and, for the intrahepatic CCs, the aspect of background liver (normal versus cirrhosis). The aim of the study was to characterize the molecular heterogeneity of CCs by a global proteomic approach. Experimental design: Thirty‐three tumor samples from 17 intrahepatic CCs (iCC) (9 developed on normal (iCCN ) and 8 developed in cirrhotic liver (iCCC )); 5 hilar CCs (CCH ); 5 pancreatic CCs (CCP ) and 6 hepatocellular carcinomas (HCC), were submitted to label‐free quantitative proteomic analysis. Differential proteins were analyzed by immunohistochemistry in a validation set of 30 CCs. Results: Unsupervised analysis revealed two main clusters: cluster 1 contained most of the iCCC while cluster 2 was divided in 2 subgroups, one containing most of the iCCN and the other regrouping CCH and CCP . Compared to iCCN, iCCC displayed upregulation of molecules involved in cell adhesion, motility and angiogenesis. Epithelial markers associated with secretory pathway and fibroblast markers were overexpressed in CCH compared to iCCN Conclusion and clinical relevance: This study demonstrated that iCCC is a specific entity, suggesting a major impact of the background liver on tumor biology, and confirmed that extrahepatic CCs define a homogeneous subgroup.